2022
DOI: 10.1111/cns.14020
|View full text |Cite
|
Sign up to set email alerts
|

Low serum magnesium is associated with poor functional outcome in acute ischemic stroke or transient ischemic attack patients

Abstract: Aim:The association between magnesium and outcomes after stroke is uncertain. We aimed to investigate the association of serum magnesium with all-cause mortality and poor functional outcome. Methods:We included patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) from the China National Stroke Registry III. We used Cox proportional hazards model for all-cause mortality and logistic regression model for poor functional outcome (modified Rankin Scale [mRS] 2-6/3-6) to examine the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
(122 reference statements)
1
1
0
Order By: Relevance
“…Subgroup analysis revealed that the association between glycemic gap and stroke recurrence was significant in DM and marginally significant in patients without DM, which might indicate that both uncontrolled DM and stress‐induced hyperglycemia in patients without DM could induce the development of stroke recurrence. Besides, the rates of mortality (11.0%) 2 and favorable functional outcome (81.6%) 29 were similar to previous reports, and a higher glycemic gap was related to an increased risk of mortality and a reduced likelihood of favorable functional outcome. Roberts et al suggested that stress hyperglycemia was associated with poor functional outcome in patients with ischemic stroke 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Subgroup analysis revealed that the association between glycemic gap and stroke recurrence was significant in DM and marginally significant in patients without DM, which might indicate that both uncontrolled DM and stress‐induced hyperglycemia in patients without DM could induce the development of stroke recurrence. Besides, the rates of mortality (11.0%) 2 and favorable functional outcome (81.6%) 29 were similar to previous reports, and a higher glycemic gap was related to an increased risk of mortality and a reduced likelihood of favorable functional outcome. Roberts et al suggested that stress hyperglycemia was associated with poor functional outcome in patients with ischemic stroke 30 .…”
Section: Discussionsupporting
confidence: 89%
“…Despite magnesium's widespread presence in food sources, magnesium deficiency remains prevalent globally, even in developed nations [ 7 ]. The 2015-2020 dietary guidelines for Americans highlight that most Americans do not meet the recommended daily magnesium intake [ 8 ]. Recent studies spanning the past 15 years have linked hypomagnesemia to ischemic stroke, with reports indicating its presence in 24% of patients with acute ischemic stroke (AIS) [ 9 ] and in 20%-65% of critically ill ICU cases.…”
Section: Introductionmentioning
confidence: 99%